Design and Implementation of Force Sensation and Feedback Systems for Telepresence Robotic Arm - Akhtar Un Nisa; Saifullah Samo; Raheel Ahmed Nizamani; Areesha Irfan; Zuha Anjum; Laveet Kumar (Universitas Muhammadiyah Yogyakarta, 2022)
Humans put their own lives aside to save other human’s life and perform risky and dangerous activities. The risk can be reduced by using new technologies. This research study focuses on telepresence and teleoperation systems with motion and force control systems that replace humans in hazardous workspaces. In telepresence, the system helps humans to visualize the environment in real-time. In teleoperation, the system provides sensation to assist human beings in performing out-of-reach and dangerous operations safely as in real, providing a shadow hand to the operator. In this study, a system is developed that consists of a slave robotic arm and a master wearable device with bidirectional communication between the robotic arm and operator (master wearable device). It also presents a gesture-controlled robotic arm that uses sensors to read and translate human arm movements as commands. The slave robotic arm, senses applied force on an object and a master wearable device develops the force according to sensed force, in a result operator senses/feels the same object in the control room at distance. The slave robotic arm also mimics the operator arm to reach the proper position of an object. Several experiments were conducted with untrained personnel and satisfactory results were yielded, which showed that the motion and force replication is 90-95% accurate.